Connecting two intrinsic electron donor and acceptor moieties through distinctive π-bridging units to explore their optical and nonlinear optical properties. (December 2022) - Muhammad, Shabbir
Abstract: Boraphenalene and pyrido(2, 1, 6-de)quinolizine moieties are intrinsically electron acceptor and donor groups, owing to their electron deficient and electron rich characteristics, respectively. In the current study, quantum computations are executed for investigating the charge transfer character and nonlinear optical (NLO) response for various combinations of boraphenalene and pyrido(2, 1, 6-de)quinolizine derivatives. The effect of various π-conjugated connectors i.e. direct ring attachment (1AB ), ethylene (2AB ), acetylene (3AB ) and phenylene (4AB ) units on optical and NLO properties were studied. Density functional theory (DFT) techniques are employed for computing the responses properties for designed compounds (A, B, 1AB, 2AB, 3AB and 4AB ). From the studied compounds, 4AB exhibits the leading average second-order NLO polarizability of 954.8 × 10 -30  esu, which was about 148 times greater than para -Nitroaniline ( p- NA) molecule (a typical push-pull NLO molecule). The source of greater values of hyperpolarizability is tracked through TD-DFT computations where electronic transitions having better oscillator strengths along with lower transition energies are seen more contributing in hyperpolarizability. Additionally, the assessment of electrostatic potentials (ESPs), density of states (DOS), frontier molecular orbitals (FMOs) and transition density matrix (TDM) diagrams provide a molecular-level insight into the structures and their relationship to NLO properties of designed derivatives. Hence, the current investigation would arouse the curiosity of other scientists in the field for such different and novel strategy for designing NLO materials. Graphical abstract: Image 1